Las tarifas de gas natural en el Perú. Una comparación de modelos regulatorios - Alfredo Juan Carlos Dammert Lira (Revista de Análisis Económico y Financiero, 2020)
The primary natural gas industry is made up of three main activities: extraction, transportation, and distribution. Natural gas transportation and distribution prices are regulated in Peru. Natural gas transportation is regulated by the efficient model company method, and natural gas distribution is regulated by the efficient model company method, but assigning prices for each use (electricity generation, industry, vehicle use, and domestic consumption). ) proportional to the substitutes. This study compares natural gas distribution prices as determined in Peru with those that would be obtained under the efficient company model with cost-proportional pricing. The economic effects and recommendations are presented as conclusions.